Influence of physical training on intracellular and extracellular zinc concentrations - Víctor Toro-Román; Jesús Siquier-Coll; Ignacio Bartolomé; Francisco J. Grijota; Diego Muñoz; Marcos Maynar-Mariño (Journal of the International Society of Sports Nutrition, 2022)
Background Physical exercise affects zinc (Zn) homeostasis. This study aimed to analyze the influence of physical training on extracellular (serum, plasma, and urine) and intracellular (erythrocytes and platelets) concentrations of Zn. Methods Forty young men, divided into a training group (TG; n = 20; 18.15 ± 0.27 years; 68.59 ± 4.18 kg; 1.76 ± 0.04 m) and a control group (CG; n = 20; 19.25 ± 0.39 years; 73.45 ± 9.04 kg; 1.79 ± 0.06 m), participated in this study. The TG was formed by semiprofessional soccer players from a youth category with a regular training plan of 10 h/week. The CG was formed by healthy men who did not practice physical exercise and had not followed any specific training plan. Plasma, serum, urine, erythrocyte, and platelet samples of Zn were obtained and analyzed by inductively coupled plasma mass spectrometry. Results The TG showed elevated plasma Zn concentrations (p < 0.01) despite similar intakes. However, TG showed reduced absolute (p < 0.01) and relative (p < 0.05) Zn concentrations in erythrocytes. Conclusions Athletes who underwent regular physical training showed elevated plasma and reduced erythrocyte Zn concentrations despite similar intakes to the CG.